The influence of climate on age at menarche: Augmented with the influence of ancestry - Sohn, Kitae (Elsevier GmbH - Urban und Fischer, 2016)
© 2016 Elsevier GmbHSamples representative of South Korea, Indonesia, and Peninsular Malaysia were analyzed and the influence of climate on age at menarche was investigated. The sample size was 24,651 for Korea (birth years 1941–1992), for Indonesia 8331 (birth years 1944–1988) plus 20,519 (birth years 1978–1997), and 2842 for Peninsular Malaysia (birth years 1927–1968). Respondents recalled their age at menarche. The mean age at menarche was calculated for each birth year by country, and for Malaysia, additionally by ancestry. It has been found that mean ages at menarche for the early birth years were much younger in Indonesia than in Korea despite similar levels of socioeconomic conditions (proxied by GDP per capita). For example, for the birth year 1944, the mean age at menarche was 14.45 years for Indonesia and 16.19 years for Korea—a difference of 1.74 years. It was necessary to double the Korean GDP per capita to make the Korean mean age at menarche the same as the Indonesian one. Chinese and Malay women in Peninsular Malaysia were further analyzed, and the results provided indirect evidence that the difference between Korea and Indonesia was not due to ancestry differences. Results in multivariate settings provided consistent results. It has been concluded that climate exerts a significant influence on age at menarche because the relatively easy availability of food in the tropics increases energy intake while the absence of cold weather decreases energy expenditure on maintenance and activity.